Does the length of institutionalization matter? Longitudinal follow‐up of persons with severe mental illness 65 years and older: shorter‐stay versus longer‐stay. (24th February 2021) - Finkel, Deborah; Bülow, Pia H; Wilińska, Monika; Jegermalm, Magnus; Torgé, Cristina Joy; Ernsth Bravell, Marie; Bülow, Per
Abstract: Objectives: As part of the process of de‐institutionalization in the Swedish mental healthcare system, a reform was implemented in 1995, moving the responsibility for services and social support for people with severe mental illness (SMI) from the regional level to the municipalities. In many ways, older people with SMI were neglected in this changing landscape of psychiatric care. The aim of this study is to investigate functional levels, living conditions, need of support in daily life, and how these aspects changed over time for older people with SMI. Methods: In this study we used data from surveys collected in 1996, 2001, 2006, and 2011 and data from national registers. A group of older adults with severe persistent mental illness (SMI‐O:P) was identified and divided into those who experienced shorter stays (less than 3 years) in a mental hospital ( N  = 118) and longer stays ( N  = 117). Results: After correcting for longitudinal changes with age, the longer‐stay group was more likely than the shorter‐stay group to experience functional difficulties and as a result, were more likely to have experienced 're‐institutionalization' to another care setting, as opposed to living independently. Conclusions: The length of mental illness hospitalization has significant effects on the living conditions of older people with SMI and their ability to participate in social life. Key Points: Mixed results from previous studies of the impact of deinstitutionalization may have resulted from limited follow‐up period and the lack of adjustment for natural processes of ageing that occur and the era in which the hospitalization primarily occurred After correction for the effects of ageing, older adults with severe mental illness and more accumulated time in a mental hospital demonstrated decreased functioning and increased need for support over time, compared to older adults with severe mental illness but less time in a mental hospital The longer‐stay group was much more likely to have been hospitalized prior to the 1980s, when significant changes in care began to be implemented It is important for clinical practice to be aware of the lingering effects of long‐term stay in mental hospitals under potentially out‐dated treatment methods and expectations